2011
DOI: 10.1557/opl.2011.572
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Micro-mechanical Properties of Soft Biological Tissues with Scanning Acoustic Microscopy

Abstract: In this study we have established a new approach to more accurately map acoustic wave speed (which is a measure of stiffness) within soft biological tissues at micrometer length scales using scanning acoustic microscopy. By using thin (5 μm thick) histological sections of human skin and porcine cartilage, this method exploits the phase information preserved in the interference between acoustic waves reflected from the substrate surface as well as internal reflections from the acoustic lens. A stack of images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…In contrast to most other studies dealing with acoustic microscopy of soft tissues, 25-33 we were able to estimate c and Z from a single measurement. This allowed a direct pixel-by-pixel derivation of mechanical properties such as K and ρ. K is related to the Young’s modulus together with Poisson’s ratio (or shear modulus).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In contrast to most other studies dealing with acoustic microscopy of soft tissues, 25-33 we were able to estimate c and Z from a single measurement. This allowed a direct pixel-by-pixel derivation of mechanical properties such as K and ρ. K is related to the Young’s modulus together with Poisson’s ratio (or shear modulus).…”
Section: Discussioncontrasting
confidence: 61%
“…SAM was applied successfully to characterizing various soft tissues and disease states. 25-35 However, only a few studies have reported SAM measurements for ocular tissues. In a previous study by our group, we reported fine-resolution, acoustical-property maps of the murine Re at a 250-MHz center frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Active area of the transducer surface is defined by a small dot of gold (electrode), which is exactly opposite to the focusing surface. Plane acoustic waves generated by transducer travel through the disc and when they cross the spherical interface between the lens and the fluid are refracted towards the focus on the axis of the lens 20,21 . Focal length (f) of an AL immersed in water is similar to that in an optical system and can be calculated from equation 1-…”
Section: Introductionmentioning
confidence: 99%